2008
DOI: 10.1103/physrevlett.100.064503
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of Energy Flux in Wave Turbulence

Abstract: The key governing parameter of wave turbulence is the energy flux that drives the waves and cascades to small scales through nonlinear interactions. In the inertial range, the energy flux is conserved across the scales, and is assumed to be constant in most theoretical approaches. It is only recently that measurements of the injected power into wave turbulence have been performed at the scale of the wave maker (integral scale). In this review, we focus on the statistical properties of the injected power fluctu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
98
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(116 citation statements)
references
References 36 publications
18
98
0
Order By: Relevance
“…For all values of D and γ, the PDFs exhibit two asymmetric exponential tails and a cusp near I ≃ 0. Note that this typical PDF shape has been also observed in various more complex systems (granular gases [10], wave turbulence [22] and convection [12,28]). As shown in Fig.…”
Section: Statistical Properties Of the Injected Powersupporting
confidence: 62%
See 1 more Smart Citation
“…For all values of D and γ, the PDFs exhibit two asymmetric exponential tails and a cusp near I ≃ 0. Note that this typical PDF shape has been also observed in various more complex systems (granular gases [10], wave turbulence [22] and convection [12,28]). As shown in Fig.…”
Section: Statistical Properties Of the Injected Powersupporting
confidence: 62%
“…The asymmetry is driven by the damping rate: The more the mean dissipation increases, the less the negative events of injected power occur. This electronic circuit is one of the simplest system to understand the properties of the energy flux fluctuations shared by other dissipative out-ofequilibrium systems (such as in granular gases [10], wave turbulence [22] and convection [12,28]). …”
Section: Introductionmentioning
confidence: 99%
“…We can then compute the integral over ω by using Cauchy's residue theorem, which requires to locate the poles of χ(ω) in the complex frequency plane (they are not restricted to be in the lower half plane, in contrast with the poles of the causal response function χ(ω)). Fortunately, this nontrivial task has already been accomplished in I in order to calculate the quantitẏ S J ≡ lim t→∞ (1/t) ln J t / J t involved in the second-lawlike inequality (26) obtained from time reversal (we recall that the Jacobian J [X] becomes a path-independent quantity J t when the dynamics is linear [6]). Specifically, it was shown in I [Eq.…”
Section: Calculation Of the (Boundary-independent) Scgfmentioning
confidence: 99%
“…Interestingly, many experimental and theoretical results have shown that deviations from wave-turbulence predictions can be found for rare events, e.g. intermittency [8,[25][26][27][28][29]. This seems to be the case when a more general theoretical framework [30][31][32][33][34] is required, because the nonlinearities are not small [35,36].…”
mentioning
confidence: 99%